United States : Financial Sector Assessment Program-Detailed Assessment of Observance on the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Detailed Assessment of Observance of the Insurance Core Principles on the United States. The assessment finds a reasonable level of observance of the Insurance Core Principles. There are many areas of strength, including at state level the powerful capacity for financial analysis with peer group review and challenge through the processes of the National Association of Insurance Commissioners. Lead state regulation is developing and a network of international supervisory colleges has been put in place. Key areas for development include the valuation standard of the state regulators, especially for life insurance, and group capital standards.